Kawasaki disease in Thai infants compared with older children - Sittiwangkul R. (2014)
Infants with Kawasaki disease (KD) are at increased risk of having coronary artery abnormalities (CAA). The purpose of this study was to evaluate the clinical features of KD in infants and compare these with findings in older children to determine the risk factors for CAA in infants. All children with KD admitted to a tertiary care hospital between January 1993 and April 2003 were studied retrospectively. Of a total of 51 patients included in the study, 22 (43%) were < 1 year of age (mean 8 months, range 2-12 months). All had classical clinical manifestations such as fever, skin rash and mucositis; extremity change occurred in 95%, conjunctivitis in 81% and cervical lymphadenopathy in 27%. Infants had significantly more non-classical symptoms, e.g. diarrhoea (68%), than older children (38%) (p=0.04). The mean number of days before intravenous immunoglobulin (IVIG) treatment was given to infants was 2 days later than in older children. The predictors of CAA in infants were resistance to IVIG treatment (p=0.02) and long duration of fever (p=0.009). Compared with older children, the less typical presentations and delay in diagnosis and treatment in infants might be important factors in CAA in KD. © 2004 The Liverpool School of Tropical Medicine.